Colectomy rates for ulcerative colitis in England 2003‐2016. Issue 4 (2nd December 2020) - Worley, Guy; Almoudaris, Alex; Bassett, Paul; Segal, Jonathan; Akbar, Ayesha; Ghosh, Subrata; Aylin, Paul; Faiz, Omar
Summary: Background: Temporal trends in colectomy rate for ulcerative colitis (UC) are particularly relevant in the current era of published IBD standards and changing approach to salvage of acute severe disease. Aims: To investigate temporal trends in colectomy for UC using English population data. Methods: The Hospital Episode Statistics (HES) were interrogated between 2003‐2016 with two patient groups investigated independently. An 'emergency' cohort: emergency UC admission ≥ three days, age ≥18 and a 'total population' cohort: all English patients undergoing colectomy for UC. Mixed methods analyses were utilised. Results: Emergency cohort: 37 981 patients, 49% female, median age 46. The one‐ and three‐year incidence of colectomy after acute admission was 0.17 and 0.21. Interrupted time series (ITS) analysis suggested reductions in colectomy rate of 4% per year after 2008 at 30 and 90 days following emergency admission, with no significant reduction ≥1 year. Mortality and laparoscopy rates improved when avoiding colectomy at index and emergency admissions; however, the proportion of emergency colectomies after salvage at index admission significantly increased during the study period. Total population cohort: 17 580 patients underwent colectomy for UC between 2003 and 2016, demonstrating a 3.1% annual reduction in total and elective colectomies after 2008, but no reduction in emergency colectomies. Conclusion: Reductions in short‐term colectomy rates after emergency admission for UC do not persist beyond one year. Emergency colectomy rates remain unchanged. Reduced rates are probably due to multi‐modal improvements in IBD care. A lack of data regarding disease severity precludes further interpretation of appropriate medical salvage and timely surgery. Abstract : Audio Podcast